MANAGEMENT OF SEED BORNE MYCOFLORA OF SORGHUM BY USING FUNGICIDES AND BIOAGENTS (Journal of Plant Disease Sciences, 2025)
Sorghum (Sorghum bicolor L.), a crucial cereal crop of arid and semi-arid regions, is frequently affected by seed-borne fungi that adversely influence seed germination and reduce crop productivity. The present study focused on the fungicidal management of seed-borne mycoflora of sorghum using the poisoned food technique. The major fungal pathogens isolated from sorghum seeds were Fusarium moniliforme, Alternaria alternata and Curvularia lunata.Among the fungicides evaluated, carboxin + thiram 75% WP was the most effective, exhibiting the highest inhibition of Fusarium moniliforme with 82.22% at 0.15%, 85.55% at 0.30% and 88.88% at 0.45% concentrations. Metalaxyl 35% WS followed, showing 73.77%, 78.14% and 85.55% inhibition at 0.10%, 0.20% and 0.30% concentrations, respectively. Fluxapyroxad 33 g L⁻¹ FS and sulphur 80% WP showed moderate effectiveness, while metalaxyl 8% + mancozeb 64% WS was the least effective. Against Alternaria alternata, carboxin + thiram 75% WP achieved 100% inhibition at all concentrations, followed by fluxapyroxad, which recorded complete inhibition at the highest concentration. Metalaxyl-based formulations exhibited moderate inhibition, whereas sulphur 80% WP was the least effective. Among the biocontrol agents, Trichoderma harzianum showed the highest inhibition against both Fusarium moniliforme (68.36%) and Alternaria alternata (74.41%), followed by Trichoderma asperellum and Bacillus subtilis, while Pseudomonas fluorescens was the least effective.
Keywords: Bioagents, Fungicide, Mycoflora, Sorghum, Management